Visual Language as a Mean of Communication in the Field of Information Technology; Information, Intelligence, Systems and Applications (IISA) - Moiseenko A. V. Aleksandr Vladimirovich; Brylina I. V. Irina Vladimirovna; Kornienko A. A. Alla Alexandrovna; Berestneva O. G. Olga Grigorievna; Kabanova N. N. Natalia Nikolaevna (2015, 2015)
Title screen